Protective Effects of Ursodeoxycholic Acid on Valproic Acid Induced Hepatotoxicity in Epileptic Children with Recurrent Seizure; A Double-Blinded Randomized Clinical Trial - Iraj Shahramian; Ali Bazi; Rosa Mostafaee; Mohammad Hasan Mohammadi (Tabriz University of Medical Sciences, 2020)
Background: There are controversies regarding the protective role of ursodeoxycholic acid (UDCA) against valproic acid (VPA)-induced hepatotoxicity in children. In the present clinical trial, we assessed the potential role of UDCA in preventing VPA-induced fluctuations of hepatic enzymes in epileptic children with recurrent seizures.Methods: Two-hundred children with epileptic seizures were randomly allocated into either intervention (VPA+UDCA) or control (VPA+ placebo) group. Fluctuations of liver enzymes were recorded at baseline, as well as 48 hours, 1 month, and 3 months following the interventions. Results: The mean age of the patients was 7.33±2.96 years (the range of 4-16). Males and females constituted 43 (43%) and 57 (57%) subjects in each group respectively. There were no significant differences in the baseline levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) between the intervention and control groups. At 48 hours post-intervention, AST and ALT increased 1.7% and 11.05% (23.18±7.91 and 30.75±4.20 IU/l) in the intervention group and 21.3% and 35% (28.46±3.71 and 35.62±7.72 IU/l) in the control group respectively (P<0.0001). Both AST (P<0.001) and ALT (P=0.03) levels were significantly lower in the intervention than placebo group at 1-month post-intervention. At 3-month post-intervention; however, while AST level still was significantly higher in the control (29.87±5.41 IU/l) than intervention (21.63±6.87 IU/l, P<0.0001), ALT level was not significantly different between the two groups (32.72±5.59 IU/l and 32.01±7.89 IU/l respectively, P=0.5). Conclusion: UDCA can be an effective drug to manage VPA-induced fluctuations of hepatic enzymes in children with recurrent epileptic seizures.